Legal Protection for Female Workers Who Are Unilaterally Laid Off by the Company - Masitah Pohan; Rahmayanti (Faculty of Law, Universitas Pekalongan, 2024)
The implementation of carbon tax has been postponed twice by the government based on the mandate of Articles 13 and 17 of Law No. 7/2021 on Harmonization of Tax Regulations. However, it is unclear how long these delays will last, raising questions about compliance with existing regulations. The postponement of carbon tax implementation based on existing regulations in the Harmonization of Tax Regulations raises concerns regarding compliance with the mandate of the law. The reason for the delay given by the government also needs to be further evaluated to ensure policy consistency and transparency in decision-making. This research aims to analyze the postponement of carbon tax implementation based on the regulations listed in the Taxation Regulations Harmonization Act, as well as identify the reasons for the postponement given by the government. This research method uses normative juridical, qualitative methods by reviewing literature, related rules, and regulations,Reasons for the delay given by the government include caution against a fragile economic recovery and a spike in energy prices. However, these reasons were also used to postpone the increase in the value-added tax (PPN) rate, potentially raising questions about compliance with regulations.